Temperature regulated cooking of keropok lekor - Muhammad Naqiy Sediq Bin Ahmad (School of Manufacturing Engineering, University Malaysia Perlis, 2010)
This project is about the grilling process that will be used to cook or to roast keropok lekor. In the cooking, the temperature needed to grill the keropok lekor needs to be studied in order to produce the best keropok lekor and is cooked in the best temperature.